2012
DOI: 10.1212/wnl.0b013e318249f673
|View full text |Cite
|
Sign up to set email alerts
|

The LRRK2 G2019S mutation is associated with Parkinson disease and concomitant non-skin cancers

Abstract: Ashkenazi Jewish patients with PD who harbor the G2019S LRRK2 mutation are more likely to have a concomitant non-skin cancer than noncarriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 32 publications
6
55
1
Order By: Relevance
“…Recently, LRRK2 mutations have been found to be an important risk factor for sporadic and familial PD [24,25]. It has been shown that PD patients with LRRK2 mutations have a different profile of malignancy compared with non-carriers of LRRK2 gene mutations [26,27]. Mutation carriers had a particularly increased risk of breast cancer in both studies, and might explain part of the increased rate in breast cancer in PD patients that we and others find [2,3].…”
Section: Interpretation and Implicationssupporting
confidence: 51%
“…Recently, LRRK2 mutations have been found to be an important risk factor for sporadic and familial PD [24,25]. It has been shown that PD patients with LRRK2 mutations have a different profile of malignancy compared with non-carriers of LRRK2 gene mutations [26,27]. Mutation carriers had a particularly increased risk of breast cancer in both studies, and might explain part of the increased rate in breast cancer in PD patients that we and others find [2,3].…”
Section: Interpretation and Implicationssupporting
confidence: 51%
“…Finally, we did not have information on hormonal and reproductive factors that could confound the association between LRRK2 mutations and breast cancer. Although we did not have complete information on the BRCA1/BRCA2 mutation status of all women with PD, investigators at Sheba Medical Center 19 evaluated mutations in their breast cancer cases and found only a single BRCA1 mutation that cosegregated with the LRRK2 G2019S mutation. They separately analyzed genome-wide association study data evaluating breast cancer single-nucleotide polymorphisms in relationship to PD genes and found no suggestion of simple cosegregation or shared genetic loci 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Sinai Beth Israel Medical Center, New York). Detailed descriptions about study participants, data collection, LRRK2 genotyping and cancer outcomes for three of the centers have been published 19,20,22,23 and are summarized for all five centers in the eTable in the Supplement. Briefly, at all centers, PD patients were queried regarding demographic and lifestyle factors as well as, personal and family history of PD and other diseases, including self-reported cancer, type of cancer, and age at diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Although indirect or controversial reports about the association of PD and cancer [15,16,25,26], diabetes mellitus patients still have a potential risk for PD [11,12], and the cancer risk among PD patients may be also attributed to the prescribing medicines for PD, as the story in diabetes mellitus. This gave hint us to think of the relation of DAs to cancer, in addition to their adverse effects on treatment of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently cancer risk among the PD patients gained much attention, especially for those with a genetic linkage [15,16], and the role of parkin, the E3 ubiquitin ligase, in cancers [17]. Therefore it is nothing to be surprised at the possibility of cross-talking between neurodegeneration and neoplasms.…”
Section: Introductionmentioning
confidence: 99%